Evaluating the potential use of functional fibrosis to facilitate improved outcomes following volumetric muscle loss injury. (1st March 2022) - Dolan, Connor P.; Motherwell, Jessica M.; Franco, Sarah R.; Janakiram, Naveena B.; Valerio, Michael S.; Goldman, Stephen M.; Dearth, Christopher L.
Abstract: Volumetric muscle loss (VML) was defined as the frank loss of skeletal muscle tissue with associated chronic functional deficits. Significant effort has been dedicated to developing approaches for treating VML injuries, most of which have focused on stimulating regeneration of the affected musculature via a variety of approaches (e.g., biomaterials). VML injury induces a prolonged inflammatory response which causes fibrotic tissue deposition and is thought to inhibit de novo myofiber regeneration despite observed improvements in functional outcomes (i.e., functional fibrosis; FF). Recent approaches have sought to attenuate inflammation and/or fibrosis as a means to create a permissive environment for regenerative therapies. However, there are currently no clinically available interventions capable of facilitating full restoration of form and function following VML injury; thus, an unmet clinical need exists for a near-term interventional strategy to treat affected patients. FF could serve as an alternative approach to facilitate improved functional outcomes following VML injuries. We sought to investigate whether intentionally exploiting the concept of FF (i.e., induction of a supraphysiological fibrotic response via the delivery of a polypropylene mesh combined with TGFβ) would enhance the function of the VML affected musculature. We found that FF treatment induces enhanced fibrotic tissue deposition within the VML defect as evidenced by histological and molecular analysis. FF-treated animals exhibit improved in vivo muscle function compared to untreated control animals at 8 weeks post-injury, thus substantiating the concept that FF could serve as an efficacious approach for facilitating improved functional outcomes following VML injury. Statement of Significance: VML injuries result in long-term functional impairments and reduced quality of life for affected individuals, namely combat injured US Service members, and no clinical interventions can restore the form and function of the injured limb. Extensive efforts have been aimed at developing therapeutics to address this critical gap; unfortunately, most interventions facilitate only modest regeneration. Interestingly, improved muscle function has been observed in VML studies following treatment with a therapeutic, despite a lack of myogenic tissue formation; a phenomenon termed Functional Fibrosis (FF). Herein we exploited the concept of FF to enhance the function of VML affected musculature. This finding is significant in that the commercially available interventions used to induce FF can be translated into the clinic near-term, thus improving the standard of care for VML injuries. Graphical abstract: Image, graphical abstract